Semi-Keplerian Magnetized Accretion-Ejection Structures - Seyedeh Zeynab Mousavi; Ali Reza Khesali; Azar Khosravi (Iranian Journal of Astronomy and Astrophysics)
The structure of a thin geometrically, axisymmetric, a stationary disk around a central black hole threaded by a bipolar magnetic field has been Studied that drives jets by extracting angular momentum. In this work, it is assumed that the effect of viscosity turbulence is negligible. If the effect of viscosity turbulence is negligible and the lines of the initial magnetic field have the required curvature, the magnetic force can be the only factor that determines the material leaving the disk. A primary poloidal magnetic field is applied to the disk, which has two components r and z. The equations that describe the vertical structure of the disk in a cylindrical system have been solved. We assume that the angular velocity is not completely Keplerian and the deviation from the Keplerian rotation enters the equations. It was seen that for a smaller ejection rate (a smaller ), the deviation from the Keplerian rotation is greater. The vertical structure equations of the disk were written with the presence of the polytropic equation. The gas with polytropic state equation with different gammas is given in this paper. For all gases, the variation in the toroidal magnetic field in the vertical direction is similar and for a constant ejection rate, the monoatomic gas has a greater deviation from the Keplerian rotation. Our results show in the presence of the polytropic equation and the deviation from Keplerian rotation, the process of mass reduction in the vertical direction for diatomic gas occurs faster.